Knockdown of a Specific Circular Non-Coding RNA Significantly Suppresses Osteosarcoma Progression. (February 2023) - Wang, Shidong; Zhang, Hongliang; Li, Bo; Chen, Chenglong; Ren, Tingting; Huang, Yi; Liu, Kai; Li, Jingjing; Guo, Wei
Abstract: Osteosarcoma (OS) is a malignant mesenchymal tissue tumor known to occur in children and adolescents, and pulmonary metastasis often leads to death in these patients. The mechanism underlying OS progression remains unclear. Therefore, identifying new therapeutic targets and treatment modalities for OS is urgently needed. Abnormally expressed non-coding circular RNAs (circRNAs) are crucial for the occurrence and development of OS. The purpose of this study was to explore the expression and role of a novel circRNA circ_000203 in OS and elucidate the underlying mechanism. circ_000203 was demonstrated highly expressed in OS cell lines and tissues, and circ_000203 knockdown significantly inhibited OS progression in vitro and in vivo . Furthermore, we found that circ_000203 is a sponge of miR-26b-5p, an upstream regulator of bone morphogenetic protein receptor 2 (BMPR2). Thus, the overexpression of BMPR2 could reduce the inhibitory effect on OS progression. This indicates that knockdown of circ_000203 suppresses OS progression through microRNA (miRNA)-mediated BMPR2 downregulation. Our findings provide important insights for understanding the occurrence and development of OS.